Methods of excitation theory in flows around cavities in liquids - Буйвол, В. М. (Proceedings of National Aviation University (archive), 1999)
Considered is mathematical model of flow around cavities in liquids, excitation of various nature taken into account. Proposed is a model of concentrated action of hydrodynamic pressure applied to free sections of cavitation caverns